PENGARUH PENERAPAN MODEL SQ3R TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN DALAM PEMBELAJARAN TEMATIK SISWA KELAS IV - Haliem, Theresa Dwita; Halidjah, Siti; Sugiatno, Sugiatno (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstract The aim of this research is to describe the effect of applying the survey model, question, read, recite, and review of reading comprehension skills in thematic learning of Grade IV SDN 03 Sungai Raya Kubu Raya District. The method is used tthe experimental method, while the form of research used is nonequivalent control group design. The sample in this study was all students in grade IV Negeri Negeri 03 Sungai Raya, Kubu Raya Regency consisting of 32 students in class IVA, 32 students in class IVB, 33 students in class IVC. Data collection tools in the form of a multiple choice test totaling 45 questions. Based on data analysis, the average post-test of the experimental class was 71.46 while the average post-test of the control class was 62.75. t test results obtained = 3.67 and (? = 5% (k = n1 + n2-2 = 32 + 33-2 = 63) of 1.98, which means (3.67) ? (1.98), Ho was rejected and Ha was accepted, indicating that there was an influence of the survey model, question, read, recite, and review of students' reading comprehension skills in the thematic learning of Grade IV SDN 03 Sungai Raya Kubu Raya regency. 0.853 (high criteria) This means that it can be concluded that the survey model, question, read, recite, review of students' reading comprehension skills in the thematic learning of grade IV SDN 03 Sungai Raya Kubu Raya District. Keywords: Influence, Reading Comprehension, SQ3R Model